2004
DOI: 10.1039/b400551a
|View full text |Cite
|
Sign up to set email alerts
|

Capturing of acidic macromolecules from biological samples using a temperature-responsive polymer modified with poly-l-lysine

Abstract: We synthesized a temperature-responsive polymer, N-(isopropylacrylamide)-methacrylic acid copolymer, to which poly-l-lysine was introduced. The synthesized polymer as well as the parent polymer showed reversible soluble-insoluble changes in response to temperature changes across the lower critical solution temperature at 32 degree C in an aqueous solution. We found that the polymer efficiently captured acidic bio-macromolecules such as RNA, glycosaminoglycans and mucin-type glycoproteins in biological samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the previous paper, we reported that HA molecules having higher molecular masses than those derived from pig skin are preferable for complex formation with poly-l-lysine [27]. Low intensity of the HA peak derived from pig skin ( Fig.…”
Section: Analysis Of Hyaluronic Acid (Ha)mentioning
confidence: 88%
“…In the previous paper, we reported that HA molecules having higher molecular masses than those derived from pig skin are preferable for complex formation with poly-l-lysine [27]. Low intensity of the HA peak derived from pig skin ( Fig.…”
Section: Analysis Of Hyaluronic Acid (Ha)mentioning
confidence: 88%
“…Thermosensitive polymers can undergo significant property changes in a controlled fashion by a temperature stimulus. Thermosensitive polymers have potential in a variety of applications, such as the stationary phase in chromatography, separation of biomacromolecules, surface modification, drug delivery, and drug release. The application in a given area may require a thermosensitive polymer with a specific cloud point and, therefore, tuning the cloud point of the thermosensitive polymers is an important research subject. Random copolymerization with another hydrophilic or hydrophobic monomer is a common method used to tune the cloud point of a thermosensitive polymer.…”
Section: Introductionmentioning
confidence: 99%
“…10 When a basic chain, poly-L-lysine, was introduced to the copolymer of IPAAm and methacrylic acid, it was able to capture and recover acidic bio-macromolecules such as RNA, glycosaminoglycans and glycoproteins. 11 As well as the separation of small molecules and the affinity capturing of proteins, temperature-responsive polymers have played an important role in DNA sequencing with capillary electrophoresis (CE). 12 Capillary gel electrophoresis (CGE) can be used to separate peptides or proteins according to their molecular weights or sizes.…”
Section: Introductionmentioning
confidence: 99%